Using the Delphi method to develop the social-ecological resilience indicators of organic rice production in Thailand - Chaiteera Panpakdee; Suchint Simaraks; Chanidapa Sookcharoen (Forestry Faculty, Universitas Hasanuddin, 2022)
This paper illustrates the application of the Delphi method, which assists in the production of social-ecological resilience indicators, and which are suitable for building the resilience of organic rice production in the central portion of Northeastern Thailand. Forty-seven adept farmers were purposively selected as participants, and the Delphi method was utilized as a tool by which the participants could reveal their different opinions and ideas. They were surveyed in order to visualize an organic rice system called the ‘desirable system.’ Nevertheless, such a system must be built simultaneously with certain components, the attributes of which can enable the system to withstand all kinds of change that can take place across spatial and temporal scales. The resilience literature, which is related to agro-ecological systems, had been published online during the seven previous years, and was applied to formulate questions, which were specifically aimed at establishing components that were focused upon coping and adaptive strategies. It was discovered that the inclusion of a group discussion, which had taken place with two rounds of the Delphi method, had provided a valuable means for exchanging information and responding with feedback. Given that the processes had been entirely conducted through group discussions, the voices of a few participants were, however, lost. They were dominated by the innate power expressed by other members within the group, especially the leaders. Despite this, the Delphi method was able to achieve an adequate degree of consensus among participants and was able to lead in the direction of building resilience with a significant level of confidence, which was capable of overcoming the social-ecological complexities of organic rice production. This was evidenced by the discovery of 21 social-ecological resilience indicators, which had been constructed by the engagement. Moreover, the indicators had indeed been reliable. With the support of the consensus of the participants’ judgements, which were based on their actual contexts of organic rice production in the central portion of Northeastern Thailand, the indicators were able to be validated by statistical analyses, consisting of arithmetic means (x), standard deviations (sd), and interquartile ranges (R).